2014
DOI: 10.1037/a0032982
|View full text |Cite
|
Sign up to set email alerts
|

Working memory training and transfer in older adults: Effects of age, baseline performance, and training gains.

Abstract: Recent studies suggest that working memory training may benefit older adults; however, findings regarding training and transfer effects are mixed. The current study aimed to investigate the effects of a process-based training intervention in a diverse sample of older adults and explored possible moderators of training and transfer effects. For that purpose, 80 older adults (65-95 years) were assigned either to a training group that worked on visuospatial, verbal, and executive working memory tasks for 9 sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
164
4
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(195 citation statements)
references
References 55 publications
17
164
4
6
Order By: Relevance
“…It supports also other work of Borella and collaborators that showed significant training and transfer effects not only in a sample of young-old adults (age range 65 to 75 years; Borella et al 2010) but also in old-old adults (age range 75 to 87 years; Borella et al 2013). However, these findings contrast an earlier study that reported smaller training and transfer gains with increasing age in older adults and no influence of crystallized abilities (Zinke et al 2014); however, Zinke et al (2014) trained much older adults than our study. The findings of both studies together indicate that age and basic cognitive abilities such as crystallized intelligence might play an important role for training outcomes in younger older adults (see also Borella et al 2017 for a similar finding).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…It supports also other work of Borella and collaborators that showed significant training and transfer effects not only in a sample of young-old adults (age range 65 to 75 years; Borella et al 2010) but also in old-old adults (age range 75 to 87 years; Borella et al 2013). However, these findings contrast an earlier study that reported smaller training and transfer gains with increasing age in older adults and no influence of crystallized abilities (Zinke et al 2014); however, Zinke et al (2014) trained much older adults than our study. The findings of both studies together indicate that age and basic cognitive abilities such as crystallized intelligence might play an important role for training outcomes in younger older adults (see also Borella et al 2017 for a similar finding).…”
Section: Discussioncontrasting
confidence: 56%
“…Similarly, metaanalyses (Karbach and Verhaeghen 2014;Soveri et al 2017) did not find differences regarding training improvement between younger and older adults. However, comparing young-old with old-old adults, Zinke et al (2014) revealed that the moderating effect of age did emerge within the group of older adults.…”
Section: Person-specific Influences On Working Memory Training Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…A closely related yet potentiallydistinct factor possibly contributing tothese mixed findings is general cognitive functioning (von Bastian and Oberauer 2014). Only few studies have directly assessed the effect of baseline cognitive performance on training outcomes though, with some evidence suggesting that initially lowperforming individuals benefit more from training (e.g., Jaeggi et al 2008;Zinke et al 2014), but others reported opposite effects (e.g., Bürki et al 2014).Although motivation is arguably one of the most plausible factors possibly influencing cognitive training outcomes, its association with training performance has not yet been comprehensively examined. One exception is a study by Brose et al (2012), whoreported a positive associationbetween dailymotivation and daily cognitive performance on a 3-back task, indicating that on days on which task-related motivation was lower than on average, daily cognitive performance was also reduced.…”
mentioning
confidence: 99%